Is the BasicsCard "shaming" Aboriginal people? Exploring the differing responses to welfare quarantining in Cape York. Issue 1 (29th December 2019) - Watt, Elizabeth
Abstract: As part of the Cape York Welfare Reform Trial (CYWRT), which has been running in the remote Aboriginal towns of Aurukun, Hope Vale, Mossman Gorge and Coen since 2008, Family Responsibilities Commissioners have the unprecedented ability to quarantine welfare payments. Critics claim these "BasicCards, " which cannot be spent on alcohol, tobacco, pornography or gambling, brings shame to Aboriginal people – marking them as dependants, deemed incapable of responsible spending. Evaluations of the CYWRT paint a more complicated picture. While many of the "spectators" of the CYWRT report "welfare reform stigma, " the "subjects" themselves are more positive. This paper draws on ethnographic research in Hope Vale to argue that these categories overlap with loosely defined, porous social groups that developed during the town's mission past, described as the "engaged" and "embedded" Hope Valers, respectively. The engaged group tends to be more aware of and sensitive to the views of the dominant society and to subscribe to its "ideology of respectability." Meanwhile, the latter group tends to adhere to a more egalitarian "ideology of relatedness, " and do not experience the shame, even when their own welfare is quarantined, because the behaviours that trigger quarantining are normalised within their highly circumscribed domain.